On the opposite Way of the Avant-Garde Aesthetic: Perfume: The Story of a Murderer, by Patrick Suskind - Volobuef, Karin [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2015)
This paper analyzes the novel Perfume: The Story of a Murderer, by Patrick Suskind, best-seller of the eighties, characterized by the recovery of traits of the nineteenth-century narrative: omniscient narrator, social and psychological analysis, description of the physical space and human aspects, creating a closed world in which events and values are explained and consistent. Suskind , however, not only works with these characteristics of nineteenth-century narrative; he also uses intertextuality and devices of serie noire (thriller), historical narrative, and supernatural stories. Shifting the interest from the crime to the criminal, a protagonist whose sense of smell is superhuman, the writer makes his novel become similar to the black novel, building a work marked by the pleasure of storytelling.
Keywords: Hybrid narrative; Perfume: The Story of a Murderer; Patrick Suskind; Novel; Supernatural